Emergence of Hypervirulent ST11-K64 Klebsiella pneumoniae Poses a Serious Clinical Threat in Older Patients - Tian Wei; Chengyun Zou; Jie Qin; Jianmin Tao; Li Yan; Jiangjun Wang; Hong Du; Fang Shen; Yanqin Zhao; Haiying Wang (Frontiers Media S.A., 2022)
The carbapenem-resistant hypervirulent Klebsiella pneumoniae (CR-hvKP) poses a severe therapeutic challenge to global public health, and research on CR-hvKP in older patients remain limited. In this study, we aimed to investigate the clinical and molecular characteristics and risk factors of CR-hvKP infections in older patients. We retrospectively investigated older patients with carbapenem-resistant Klebsiella pneumoniae (CRKP) infections in the intensive care unit (ICU) between January 2020 and December 2020. The clinical data, and microbiological data including antimicrobial susceptibility testing, phenotype experiment and detection of carbapenemases, string test, virulence genes, capsular serotype-specific (cps) genes, and multilocus sequence typing, of the CR-hvKP group defined by the presence of any one of the virulence genes, including rmpA, rmpA2, iucA, iroN, and peg-344 were compared with those of CR-non-hvKP strains. Of the 80 CRKP strains, 51 (63.8%) met the definition of CR-hvKP. The main mechanism of resistance to carbapenems was the presence of the blaKPC−2 gene. Sequence type (ST)11 (81.3%, 65/80) and ST15 (16.3%, 13/80) were the most common STs in CRKP strains. The minimum inhibitory concentration (MIC)50 values of the CR-hvKP group against the six tested antibiotics (ceftazidime, ceftazidime-avibactam, imipenem-avibactam, tigecycline, levofloxacin, and Cefoperazone-Sulbactam) exhibited elevated levels than the CR-non-hvKP group. Ceftazidime and imipenem by combining avibactam (4 μg/mL) significantly decreased the MIC90 values more than 16-fold than ceftazidime and imipenem alone against Klebsiella pneumoniae carbapenemase (KPC)-2-producing K. pneumoniae. Cardiovascular disease [odds ratio (OR) = 11.956] and ST11-K64 (OR = 8.385) appeared to be independent variables associated with CR-hvKP infection by multivariate analysis. In conclusion, higher MICs of the last line antibiotic agents (ceftazidime-avibactam, tigecycline) might be a critical consideration in the clinical management of older patients where the concentration of these toxic antibiotics matters because of underlying comorbidities. Caution regarding KPC-2-producing ST11-K64 CR-hvKP as being new significant "superbugs" is required as they are widespread, and infection control measures should be strengthened to curb further dissemination in nosocomial settings in China.